A situation analysis of children & women in Bhutan, 2006 - Black, Maggie, 1945- (UNICEF, 2006)
Evaluation of the ground realities of child and women development; study conducted by UNICEF Bhutan in close collaboration of National Commission for Women & Children, Bhutan.